Las venas de los lirios" De místicas, visionarias y santas vivas en la Literatura de Granada (ss. xv1-xx) - García Suarez, Pedro (Arenal-Revista De Historia De Las Mujeres, 2024)
[Resumen no disponible]
The veins of the lilies Of mystics, visionaries and living saints in the Literature of Granada (16th to 20th Centuries)
Keywords: reseña; mujeres; literatura; granada; misticas